Early Changes in Nutritional Conditions Affect Formation of Synthetic Mutualism Between Chlorella sorokiniana and the Bacterium Azospirillum brasilense - Palacios, Oskar A.; Lopez, Blanca R.; Bashan, Yoav; de-Bashan, Luz E. (Microbial ecology, 2019)
The effect of three different nutritional conditions during the initial 12 h of interaction between the microalgae Chlorella sorokiniana UTEX 2714 and the plant growth–promoting bacterium Azospirillum brasilense Cd on formation of synthetic mutualism was assessed by changes in population growth, production of signal molecules tryptophan and indole-3-acetic acid, starch accumulation, and patterns of cell aggregation. When the interaction was supported by a nutrient-rich medium, production of both signal molecules was detected, but not when this interaction began with nitrogen-free (N-free) or carbon-free (C-free) media. Overall, populations of bacteria and microalgae were larger when co-immobilized. However, the highest starch production was measured in C. sorokiniana immobilized alone and growing continuously in a C-free mineral medium. In this interaction, the initial nutritional condition influenced the time at which the highest accumulation of starch occurred in Chlorella, where the N-free medium induced faster starch production and the richer medium delayed its accumulation. Formation of aggregates made of microalgae and bacteria occurred in all nutritional conditions, with maximum at 83 h in mineral medium, and coincided with declining starch content. This study demonstrates that synthetic mutualism between C. sorokiniana and A. brasilense can be modulated by the initial nutritional condition, mainly by the presence or absence of nitrogen and carbon in the medium in which they are interacting.